Foam made using silicone functionalized polyethylene and method for making the same
By using a composition of silicone functionalized polyethylene and a physical foaming agent, the problem of low foaming efficiency of low-density ethylene polymer foam in the prior art is solved, foam with a density less than 0.200 g/cc is achieved, and it can have improved foaming agent efficiency and structural flexibility.
Patent Information
- Application Number
- CN202180068960.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-16
- Filing Date
- 2021-09-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-09-16
AI Technical Summary
Prior art In the preparation of low-density ethylene polymer foams, foaming efficiency is low and is generally limited to closed cell structures, especially when prepared by extrusion methods.
The extruded foam is formed by using a composition containing silicone functionalized polyethylene and a physical foaming agent, with a copolymerization product of functionalized polydimethylsiloxane and polyethylene, and a density of less than or equal to 0.200 g/cc under the ASTM D1622-88 standard.
An improved foaming agent efficiency is achieved, with a lower density, and may have an open or closed cell structure compared to foams without silicone functionalized polyethylene.
Smart Images

Figure FDA0005171191660000011 
Figure GDA0005145382870000021 
Figure GDA0005145382870000061
Abstract
Description
Technical Field
[0001] Embodiments of the present disclosure relate generally to ethylene polymer foams, and more particularly to foams made using silicone-functionalized polyethylene. Background Art
[0002] Less than 0.200g / cm 3 Conventional polyethylene foams of density (referred to as "low density foams") can be prepared by a variety of methods and using a variety of polymers. However, the methods for preparing such foams may exhibit low foaming efficiency. Additionally, such foams are generally limited to closed cell structures, particularly when prepared by extrusion methods.
[0003] Therefore, there is a need for alternative vinyl polymer foams. Summary of the invention
[0004] The present disclosure satisfies these needs by providing extruded foams formed from compositions comprising silicone functionalized polyethylene comprising functionalized polydimethylsiloxane combined with polyethylene and a physical blowing agent. In embodiments, the foam has a density less than or equal to 0.200 g / cc as measured at 25° C. according to ASTM D1622-88. Such foams may have an open or closed cell structure and, in embodiments, exhibit improved blowing agent efficiency (i.e., lower density) compared to foams without silicone functionalized polyethylene using the same amount of blowing agent.
[0005] According to a first embodiment of the present disclosure, an extruded foam is formed from a composition comprising: 1 wt % to 99 wt % of a silicone functionalized polyethylene comprising a polymerization reaction product of ethylene and a (meth)acrylate functionalized polydimethylsiloxane; and a physical blowing agent; wherein the foam has a density less than or equal to 0.200 g / cm3 as measured at 25°C according to ASTM D1622-88.
[0006] According to a second embodiment, the extruded form comprises an extruded foam according to the previous embodiment, wherein the silicone functionalized polyethylene has a polydispersity index (PDI) of 3 to 14.
[0007] According to a third embodiment, the extruded form comprises an extruded foam according to any one of the preceding embodiments, wherein the silicone functionalized polyethylene comprises one or more of the following structures:
[0008]
[0009] wherein R is methyl or hydrogen, R1 is a bridge group connecting the functional group ((meth)acrylate) and siloxane, R2 is an end group selected from the group consisting of alkyl, substituted alkyl, aryl, alkenyl, H and OH, x is an integer from 10 to 1000, and y is an integer from 1 to 20.
[0010] According to a fourth embodiment, the extruded form comprises an extruded foam according to any of the preceding embodiments, wherein the composition further comprises from greater than 0 wt% to 99 wt% of an olefin polymer.
[0011] According to a sixth embodiment, the extruded form comprises an extruded foam according to any one of the preceding embodiments, wherein the olefin polymer comprises LDPE.
[0012] According to a seventh embodiment, the extruded form comprises an extruded foam according to any one of the preceding embodiments, wherein the composition further comprises from greater than 0 wt % to 2 wt % of a permeability modifier.
[0013] According to an eighth embodiment, the extruded form comprises an extruded foam according to any one of the preceding embodiments, wherein the permeability modifier comprises an amide or ester of a C10 to C24 fatty acid.
[0014] According to a ninth embodiment, the extruded form comprises an extruded foam according to any one of the preceding embodiments, wherein the physical blowing agent comprises isobutane, carbon dioxide, n-butane, isomers of pentane, hydrocarbons, or mixtures thereof.
[0015] According to a tenth embodiment, the extruded form comprises the extruded foam according to any one of the preceding embodiments, wherein the physical blowing agent is present in an amount of 5% to 20% by weight.
[0016] According to an eleventh embodiment, the extruded form comprises an extruded foam according to any one of the preceding embodiments, wherein the foam is open-celled.
[0017] According to a twelfth embodiment, the extruded form comprises an extruded foam according to any one of the preceding embodiments, wherein the foam has a viscosity of 0.090 g / cm 3 Up to 0.200g / cm 3 density.
[0018] According to a thirteenth embodiment, the extruded form comprises an extruded foam according to any one of the first to tenth embodiments, wherein the foam is closed cell.
[0019] According to a fourteenth embodiment, the extruded form comprises an extruded foam according to any one of the first to tenth or thirteenth embodiments, wherein the foam has a viscosity of 0.015 g / cm 3 Up to 0.200g / cm 3density.
[0020] These and other embodiments are described in more detail in the detailed description which follows. DETAILED DESCRIPTION
[0021] The specific embodiments of the application will now be described. However, the present disclosure can be implemented in different forms and should not be construed as being limited to the embodiments set forth in the present disclosure. On the contrary, these embodiments are provided so that the present disclosure will be thorough and complete, and will fully convey the scope of the subject matter to those skilled in the art.
[0022] definition
[0023] Any reference to the periodic table is to the International Union of Pure and Applied Chemistry (IUPAC) periodic table.
[0024] Numerical ranges disclosed herein include all values from the upper limit to the lower limit, and include the upper limit and the lower limit. For ranges containing explicit values (e.g., 1 or 2, or 3 to 5, or 6 or 7), any sub-range between any two explicit values is included (e.g., the above ranges 1-7 include 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).
[0025] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.
[0026] The term "composition" refers to a mixture of materials comprising the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0027] The terms "comprises," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. Conversely, the term "consisting essentially of excludes any other components, steps, or procedures from the scope of any subsequent listing, except those that are not essential to operability. The term "consisting of" excludes any components, steps, or procedures not specifically described or listed. Unless otherwise stated, the term "or" refers to the members listed individually as well as in any combination. The use of the singular includes the use of the plural, and vice versa.
[0028] As used herein, "pendant functional group" refers to a functional group at a position other than a terminal end on the polymer backbone.
[0029] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether of the same or different types, which monomers, in polymerized form, provide the multiple and / or repeating "units" that make up the polymer. Thus, the generic term polymer encompasses the term "homopolymer," which is usually used to refer to polymers prepared from only one type of monomer, as well as "copolymer," which refers to polymers prepared from two or more different monomers. It should be noted that although polymers are often referred to as being "made from" one or more specified monomers, "based on" a specified monomer or monomer types, "containing" a specified monomer content, etc., in the present context, the term "monomer" is understood to refer to the polymerized residue of the specified monomer.
[0030] As used herein, the term "blend" or "polymer blend" refers to a mixture of two or more polymers. A blend may be miscible or may not be miscible (not phase separated at the molecular level). A blend may or may not be phase separated. A blend may be achieved by physically mixing two or more polymers at the macroscopic level (e.g., melt blending resins or compounding) or at the microscopic level (e.g., simultaneously formed in the same reactor).
[0031] As used herein, the term "terminal olefin group" refers to a double bond between two carbon atoms in a polymer chain, wherein one of the carbons in the double bond is a =CH2 group. The terminal double bond is located at the end of the polymer chain and / or at the branched end of the polymer chain. As used herein, the term "internal olefin group" refers to a 1,2-disubstituted carbon-carbon double bond, with the carbon atoms in a trans configuration (not a cis configuration). Terminal olefin groups and internal olefin groups are measured by infrared spectroscopy ("IR").
[0032] As used herein, "olefin-based polymers" or "polyolefins" or "olefin polymers" are polymers that contain more than 50 weight percent polymerized olefin monomers (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Non-limiting examples of olefin-based polymers include ethylene-based polymers and propylene-based polymers (such as polypropylene).
[0033] "Polyethylene" or "ethylene polymer" or "ethylene-based polymer" shall mean a polymer comprising more than 50 mole % of units derived from ethylene monomers. This includes polyethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of polyethylene known in the art include low density polyethylene (LDPE); linear low density polyethylene (LLDPE); ultra low density polyethylene (ULDPE); very low density polyethylene (VLDPE); medium density polyethylene (MDPE); and high density polyethylene (HDPE).
[0034] The term "LDPE" may also be referred to as "high pressure ethylene polymer" or "highly branched polyethylene" and is defined to mean a polymer partially or completely homopolymerized or copolymerized in an autoclave or tubular reactor at pressures above 14,500 psi (100 MPa) by using a free radical initiator such as a peroxide (see, e.g., US 4,599,392). LDPE resins typically have a density in the range of 0.916 g / cm to 0.935 g / cm.
[0035] As used herein, the term "silicone" includes polysiloxanes and low molecular weight siloxanes. In an embodiment, the siloxane is polydimethylsiloxane (PDMS) having various end groups as described below.
[0036] As used herein, "cell density" refers to the number of foam cells per unit volume of the foam composition.
[0037] As used herein, the term "closed cell foam" is a foam in which the foam cells are separated by a membrane wall of polymeric material having no openings. The closed cell volume is not as easily in fluid communication with the atmosphere outside it as with open cell foam. As used herein, the term "open cell foam" is a foam in which (i) there are no membrane walls of polymeric material separating the foam cells or (ii) there are openings in the membrane wall of polymeric material. The open cell volume is in fluid communication with the atmosphere outside it.
[0038] As used herein, the terms "foam" and "foam composition" refer to a structure composed of a polymer and comprising a plurality of channels extending from a surface of the structure into the structure and through the structure. The channels have no direction relative to the longitudinal extension of the structure. The channels include a plurality of foam cells that are in fluid communication with the external atmosphere. As used herein, the terms "foam pores" or "pores" are discrete spaces within the foam composition. The foam pores are separated or otherwise defined by membrane walls of the polymer comprising the foam composition.
[0039] The term "foaming temperature" refers to the final set temperature in the cooling section or other suitable heat exchanger of the foam extruder, which is located directly upstream of the exit die. For example, the foaming temperature can be the set temperature of the last zone of the extruder used to cool the foamable composition. The set temperature may or may not be different from the extrudate (foamable composition) melt temperature measured at the exit die.
[0040] Silicone functionalized polyethylene
[0041] Various embodiments include foams prepared from compositions comprising one or more organosilicon functionalized polyethylenes and physical foaming agents. Organosilicon functionalized polyethylenes include copolymers of ethylene and functionalized polydimethylsiloxanes (f-PDMS), wherein the functionalized polydimethylsiloxanes are (meth) acrylate functionalized polydimethylsiloxanes. In some such embodiments where polyethylene is low-density polyethylene (LDPE), organosilicon functionalized polyethylenes may be referred to herein as "LDPE-to-PDMS". In an embodiment, copolymers are formed by high-pressure free radical polymerization by reacting ethylene monomers with f-PDMS, or by reacting a mixture of ethylene monomers with functionalized polysiloxanes. In an embodiment, PDMS is attached to high-pressure ethylene polymers via several covalent bonds, which are produced by the growth-growth chain reaction of the initial functional groups of the functionalized PDMS with the ethylene polymer, followed by further reaction with the ethylene monomers, and also include bridges between the functional groups and siloxanes that are polymerized. This article describes a method for preparing LDPE-to-PDMS.
[0042] In an embodiment, the LDPE-co-PDMS may include 0.1 wt % to 50 wt % PDMS, such as 0.1 wt % to 20 wt %, 0.1 wt % to 15 wt %, 0.5 wt % to 15 wt %, 3 wt % to 15 wt %, or 5.0 wt % to 15 wt %, based on the total weight of the LDPE-co-PDMS composition, which also includes LDPE formed during copolymerization but not covalently attached to PDMS.
[0043] In various embodiments, the copolymer of ethylene monomer and f-PDMS comprises LDPE-co-PDMS having one or more of the following structures, but not limited to:
[0044]
[0045] Where R is methyl or hydrogen, R 1 R is a bridge group connecting the functional group ((meth)acrylate) and the siloxane. 2 is a terminal group selected from the group consisting of an alkyl group, a substituted alkyl group, an aryl group, an alkenyl group, H and OH, x is an integer from 10 to 1000, and y is an integer from 1 to 20. R 1 and R 2 The groups may be the same or different.
[0046] In an embodiment, the bridging group of LDPE-co-PDMS is selected from substituted or unsubstituted C2-C 20Alkylene linker, wherein one or more carbon atoms can be substituted by oxygen and / or silicon, substituted or unsubstituted aryl, and derivatives and combinations thereof. In an embodiment, the functional group bound to the bridging group is bound to the high pressure ethylene polymer by polymerization with ethylene monomer. The functional group is a (meth) acrylate group. In another embodiment, the bridging group is a group described below:
[0047]
[0048] In the above structural formula, the ethylene-based polymer branches are depicted as polyethylene (PE), but it is expected that, in embodiments, the ethylene-based polymer branches can be homopolymers (e.g., LDPE) or copolymers, such as ethylene (meth)acrylate copolymers, or ethylene (meth)acrylic acid copolymers, or ethylene vinyltrimethoxysilane copolymers, or ethylene vinyl acetate copolymers.
[0049] The polymer comprises polysiloxane units, which in embodiments are derived from functionalized polydimethylsiloxane (e.g., f-PDMS). In embodiments, the functionalized polysiloxane is (meth)acrylate functionalized polymethyldisiloxane (f-PDMS), wherein the (meth)acrylate functional groups are attached to the PDMS via bridges.
[0050] Functionalized polysiloxane
[0051] Polysiloxane can be any one in the different types of polymers made as fluid, resin or elastomer.Polysiloxane is part of organic compound, but different from most of polymers, they have the main chain that does not contain carbon but is composed of alternating silicon and oxygen atoms as shown above.Although in the structural formula shown above, each silicon is illustrated as being combined with methyl and / or R group, it is expected that each in those positions can be alkyl, vinyl, phenyl, hydrogen, hydroxyl, acetoxy, alkenyloxy, oxime, methoxyl group, ethoxyl, alkoxyl, dimethylamino, aminopropyl, hydroxypropyl, mercaptopropyl, chloropropyl, acryloxypropyl, methacryloxypropyl, glycidoxypropyl or epoxycyclohexylethyl individually.In an embodiment, each position is methyl.
[0052] In some embodiments, x is sufficiently large that the polysiloxane has a viscosity of 100 or greater, 200 or greater, or 500 or greater centistokes (CST). In embodiments, x is no greater than a value that would produce a polysiloxane with a viscosity no greater than 2.5 million CST. However, it is contemplated that the upper limit of the viscosity is less than 2.5 million CST, for example, 1 million or 600,000 CST. Centistoke conversion (CST): 1 CST = 0.001 Pa·s.
[0053] Suitable polysiloxanes for use in various embodiments include those described in US Patent No. 6,239, 244. Polysiloxanes are commercially available from many different manufacturers including, but not limited to, Dow, Momentive, Wacker, Shin-Etsu, and Evonik.
[0054] The polysiloxane is a polydimethylsiloxane (PDMS) comprising one or more functional groups, and is therefore referred to as a functionalized PDMS or f-PDMS. The f-PDMS is a (meth)acrylate functionalized PDMS, wherein the (meth)acrylate group is bonded to the PDMS via a bridging group. The PDMS may be monofunctional or difunctional or multifunctional, and one or more functional groups may be attached to the end or side position of the siloxane. Therefore, in an embodiment, the f-PDMS comprises the structural formula of one of the following structures or a combination thereof:
[0055]
[0056] or
[0057]
[0058] Where R is methyl or hydrogen, R 1 is the bridge foundation, R 2 is a terminal group selected from an alkyl group, an aryl group, an alkenyl group, H or OH, x is an integer from 10 to 1000, and y is an integer from 1 to 20.
[0059] Methods - Functionalized Polysiloxanes
[0060] In various embodiments, each bridge group in the f-PDMS is determined by a method of connecting the siloxane backbone to the (meth)acrylate functional group. In embodiments, the siloxane backbone is connected to the (meth)acrylate functional group by direct hydrosilylation with alkenyl (meth)acrylates, hydrosilylation of mono- or polyvinyl PDMS using SiH-functional (meth)acrylate conversion agents, or equilibration / condensation with (meth)acrylate functional alkoxysilanes. Other methods for connecting the siloxane backbone and the (meth)acrylate functional group are contemplated and may be used, depending on the particular embodiment.
[0061] Method - Copolymers of ethylene and functionalized polysiloxanes
[0062] In various embodiments, LDPE-to-PDMS is formed in the presence of ethylene. In an embodiment, LDPE-to-PDMS is produced by a high pressure, free radical polymerization process. Two different free radical initiated high pressure polymerization process types are known. In the first process type, a stirred autoclave reactor with one or more reaction zones is used. The autoclave reactor includes several injection points for initiator or monomer feed, or both. In the second process type, a jacketed tube is used as a reactor, which has one or more reaction zones. Suitable reactor lengths include, but are not limited to, 100 meters (m) to 3000 meters, or 1000m to 2000m. The beginning of the reaction zone of either type of reactor is usually limited by the side injection of the initiator, ethylene, chain transfer agent (or telomer), one or more comonomers, or a combination thereof of the reaction. The high pressure process can be carried out in an autoclave reactor or a tubular reactor with one or more reaction zones, or in a combination of an autoclave reactor and a tubular reactor each containing one or more reaction zones.
[0063] In various embodiments, chain transfer agents (CTA) can be used to control polymer properties, including but not limited to the molecular weight and melt index of the resulting polymer. Chain transfer involves the termination of growing polymer chains, thereby limiting the ultimate molecular weight of the polymer material. Chain transfer agents are typically hydrogen atom donors that will react with the growing polymer chains and stop the polymerization reaction of the chains. For high pressure free radical polymerization, CTAs can be many different types, such as saturated hydrocarbons, unsaturated hydrocarbons, aldehydes, ketones, or alcohols. Non-limiting examples of CTAs include propylene, isobutane, n-butane, 1-butene, methyl ethyl ketone, acetone, ethyl acetate, propionaldehyde, which can be purchased under the trade name ISOPAR TM The product obtained is available from ExxonMobil Chemical Co. and isopropanol. In embodiments, the amount of CTA used in the process is from 0.01 wt % to 10 wt % of the total reaction mixture.
[0064] In an embodiment, the free radical initiator may include CTA as a solvent or as a blend injected simultaneously with ethylene. For example, CTA may be blended with ethylene, pressurized, and then injected into the reactor.
[0065] In various embodiments, one or more free radical initiators are used to produce LDPE-to-PDMS. Free radical initiators commonly used to produce ethylene-based polymers such as LDPE are oxygen and peroxide. Non-limiting examples of free radical initiators include tert-butyl peroxypivalate, di-tert-butyl peroxide, tert-butyl peroxyacetate (TPA), tert-butyl peroxyoctanoate (TPO), peroxy-2-tert-butyl hexanoate, and combinations thereof. Other initiators known and used in the art are also contemplated. In embodiments, initiator is included in conventional amounts, such as 0.005 wt % to 0.2 wt % based on the weight of polymerizable monomers. In embodiments, initiator is injected before or in the reaction zone of inducing free radical polymerization. The termination of catalyst activity can be achieved by a combination of high reactor temperatures for the free radical polymerization portion of the reaction, or by feeding the initiator dissolved in a polar solvent such as propanol, water or a conventional initiator solvent such as a mixture of branched or unbranched alkanes into the reactor. In an embodiment, a free radical initiator initiates polyethylene chain formation, which then attacks the growing chain onto a functional group (e.g., a (meth)acrylate group) of f-PDMS, followed by further reaction of the newly formed α-carbonyl radical with an ethylene monomer, thereby enabling attachment of ethylene (monomeric or polymerized form) to the (meth)acrylate.
[0066] In an embodiment, at least one hydrocarbon solvent may be included in the free radical initiator system. The hydrocarbon solvent may be, for example, C5 to C 30 Hydrocarbon solvents. Exemplary hydrocarbon solvents include, for example, but are not limited to, mineral solvents, normal paraffinic solvents, isoparaffinic solvents, cyclic solvents, and the like. In embodiments, the hydrocarbon solvent is selected from the group consisting of n-octane, isooctane (2,2,4-trimethylpentane), n-dodecane, isododecane (2,2,4,6,6,-pentamethylheptane), and other isoparaffinic solvents. Exemplary hydrocarbon solvents such as isoparaffinic solvents are commercially available from ExxonMobil Chemical Company under the trademarks ISPAR C, ISOPAR E, and ISOPAR H, for example. In embodiments, the hydrocarbon solvent accounts for less than 99% by weight of the free radical initiator system.
[0067] Embodiments may also include polar co-solvents such as alcohol co-solvents (e.g., C1 to C 30The alcohol cosolvent may be a polyol, an aldehyde, a ketone or an ester. The alcohol functional group of the alcohol cosolvent may be monofunctional or polyfunctional. Suitable alcohol cosolvents may include, for example but not limited to, isopropanol (2-propanol), allyl alcohol, 1-pentanol, methanol, ethanol, propanol, 1-butanol, 1,4-butanediol, combinations thereof, or mixtures thereof. In some embodiments, the polar cosolvent may be included in an amount less than 40% by weight of the free radical initiator system.
[0068] Other additives, such as processing aids, plasticizers, stabilizers, UV absorbers, antistatic agents, pigments, dyes, nucleating agents, fillers, slip agents, flame retardants, lubricants, smoke suppressants, viscosity control agents and anti-caking agents. In an embodiment, one or more of the additives are included in an amount less than 50% by weight of the combined weight of the additives based on the weight of the polymer.
[0069] In embodiments, the method includes a process recycle loop to further improve conversion efficiency. In such embodiments, the downstream reaction zone or zone is maintained at a temperature lower than the temperature at which the ethylene-based polymer will separate from the polysiloxane. In embodiments, the recycle loop may be treated to neutralize residues or byproducts from previous reaction cycles, as such residues or byproducts may inhibit polymerization of the polysiloxane or ethylene-based polymer.
[0070] Ethylene, f-PDMS, initiator, and CTA are each added to the reactor at one or more locations to achieve the desired ratio of components in the feed and or reaction zone of the reactor. As will be appreciated by those skilled in the art, the selection of the feed point for each component into the reactor and / or reaction zone depends on several factors, including but not limited to solubility of the component in the pressurized ethylene and / or condensation and / or fouling that may occur in the preheater used to heat the reactor contents prior to injection of the initiator.
[0071] The ethylene used to produce LDPE-co-PDMS may be purified ethylene obtained by removing polar components from a loop circulation stream or a reaction system configuration in which only fresh ethylene is used to prepare LDPE-co-PDMS polymer.
[0072] In an embodiment, polymerization is carried out in a continuous stirred tank reactor using propylene as a chain transfer agent. Ethylene and propylene are fed to the top of the reactor along the stirring shaft. In an embodiment, t-butyl peroxyacetate (TPA) and t-butyl peroxyoctanoate (TPO) are used as initiators injected into the side of the reactor. In an embodiment, f-PDMS is injected alone into the side of the reactor.
[0073] In embodiments, the maximum temperature in each reaction zone is from 150° C. to 360° C., from 170° C. to 350° C., or from 200° C. to 325° C. In embodiments, the polymerization pressure at the reactor inlet is from 100 MPa to 360 MPa, from 150 MPa to 340 MPa, or from 185 MPa to 320 MPa. After polymerization, the contents of the reactor, including unreacted reactants and LDPE-co-PDMS polymer, are discharged from the outlet of the reactor.
[0074] The LDPE-co-PDMS polymer may be separated from any remaining reactants according to any method known and used in the art. In an embodiment, atomization is used to separate the LDPE-co-PDMS polymer from the remaining reactants, and the LDPE-co-PDMS polymer is collected in powder form.
[0075] Although certain specific LDPE-to-PDMS structures are shown in the structures given herein, it is expected that other structures are possible and expected. In addition, in embodiments, LDPE-to-PDMS polymers are present in blends comprising one or more of the structures depicted herein. For example, in embodiments, in addition to attaching f-PDMS to LDPE by copolymerizing the double bonds of the functional groups with ethylene, the reaction may also produce a certain amount of byproducts, wherein LDPE is attached to PDMS through the methyl groups of PDMS via a chain transfer mechanism. In addition, it should be recognized that LDPE-to-PDMS may only constitute a certain amount of reaction products, and the majority of the reaction products are LDPE. In embodiments, LDPE-to-PDMS is present in a blend comprising at least one additional polymer. The additional polymer can be, for example, a low density polyethylene (LDPE), a linear low density polyethylene (LLDPE), an ultra low density polyethylene (ULDPE), a very low density polyethylene (VLDPE), a medium density polyethylene (MDPE), a high density polyethylene (HDPE), a copolymer comprising a (meth)acrylate, a copolymer comprising (meth)acrylic acid, a monoester or diester of maleic acid, a copolymer comprising vinyl acetate, a copolymer comprising trialkoxyvinylsilane, a grafted polyethylene, or a derivative or combination thereof.
[0076] In an embodiment, the LDPE-co-PDMS may have a molecular weight of 3.0 to 50.0, such as 3.0 to 45.0, 3.0 to 40.0, 3.0 to 35.0, 3.0 to 30.0, 3.0 to 20.0, 3.0 to 15.0, 3.0 to 10.0, 4.0 to 50.0, such as 4.0 to 45.0, 4.0 to 40.0, 4.0 to 35.0, 4.0 to 30.0, 4.0 to 20.0, 4.0 to 15.0, 4.0 to 10.0, 5.0 to 50.0, such as 5.0 to 45.0, 5.0 to 40.0, 5.0 to In some embodiments, the LDPE-co-PDMS may have a polydispersity index (PDI) of 3.0 to 14.0, 5.0 to 14.0, or 7.0 to 14.0. In some embodiments, the LDPE-co-PDMS may have a PDI of 3.0 to 14.0, 5.0 to 14.0, or 7.0 to 14.0. In an embodiment, the LDPE-co-PDMS may have a molecular weight of 0.15 g / 10 min to 500.00 g / 10 min, such as 0.15 g / 10 min to 100 g / 10 min, 0.15 g / 10 min to 25.00 g / 10 min, 0.15 g / 10 min to 10.00 g / 10 min, 0.3 to 1.7, 0.3 to 2.0, 0.3 to 3.0, 0.3 to 10 , 0.5 to 1.7, 0.5 to 2.0, 0.5 to 3.0, 0.5 to 10, 1.0 to 1.7, 1.0 to 2.0, 1.0 to 3.0, 1.0 to 10, 1.3 to 1.7, 1.3 to 2.0, 1.3 to 3.0, 1.3 to 10, 0.50 g / 10 min to 10.00 g / 10 min, or 0.50 g / 10 min to 7.50 g / 10 min. PDI is determined by "conventional GPC" or "3D-GPC".
[0077] Physical foaming agent
[0078] As noted above, in addition to the silicone-functionalized polyethylene, the foam-forming composition also includes a physical blowing agent.
[0079] As used herein, the term "physical blowing agent" is a compound or composition that (i) dissolves in a polymer composition under extrusion conditions by virtue of being sufficiently soluble in the polymer composition under those conditions, and (ii) comes out of solution at the conditions (temperature, pressure) encountered during the formation of the foam composition as the foamable composition leaves the die. The physical blowing agent is added to the polymer composition under extrusion conditions to form the foamable composition. As used herein, the term "foamable composition" is a mixture of a polymer composition and a physical blowing agent under extrusion conditions.
[0080] In embodiments, a physical blowing agent is added to the polymer composition at a location downstream from the inlet of the extruder.
[0081] As will be described herein, extrusion conditions at a temperature of 50° C. to 250° C. include sufficiently high pressures to (i) prevent the blowing agent from causing expansion of the polymer composition and / or foamable composition within the extruder or other suitable melt processing equipment, and (ii) enable the blowing agent to be uniformly dispersed within the polymer composition. In an embodiment, the extrusion conditions include a temperature of 140° C. to 200° C. and a pressure of 1.40 MPa to 3.00 MPa, or a temperature of 150° C. to 190° C. and a pressure of 1.80 MPa to 2.80 MPa, or a temperature of 160° C. to 180° C. and a pressure of 2.20 MPa to 2.60 MPa.
[0082] Non-limiting examples of suitable physical blowing agents include C 1-6 Hydrocarbons (such as acetylene, propane, propylene, n-butane, butene, butadiene, isobutane, isobutylene, cyclobutane, cyclopropane, ethane, methane, ethylene, isomers of pentane, pentene, cyclopentane, pentene, pentadiene, hexane, cyclohexane, hexene and hexadiene), C 1-5 Organic halogen, C 1-6 Alcohol, C 1-6 Ether, C 1-5 Ester, C 1-5 Amines, alcohols, ammonia, nitrogen, carbon dioxide, water, neon, helium, and combinations thereof. In an embodiment, the physical blowing agent is one or more of n-butane, isobutane, n-pentane, isopentane, neopentane, carbon dioxide, ethanol, and 1,1-difluoroethane (HFC-152a).
[0083] The physical blowing agent (e.g., isobutane) may be present in an amount of 0.5 wt % to 30 wt %, or 2 wt % to 25 wt %, or 5 wt % to 20 wt %, or 8 wt % to 15 wt %, based on the total weight of the foamable composition, depending on the particular embodiment. In embodiments, LDPE-co-PDMS exhibits improved foaming efficiency, such that the amount of physical blowing agent may be reduced to obtain a given foam density compared to a similar foamable composition (e.g., a composition comprising LDPE and a blowing agent) that does not contain LDPE-co-PDMS in the foamable composition.
[0084] In one embodiment, a chemical blowing agent is used and one or more physical blowing agents are generated by thermal decomposition in the process. Chemical blowing agents include, but are not limited to, azodicarbonamide, azobisisobutyronitrile, barium azodicarboxylate, N,N'-dimethyl-N,N'-dinitrosoterephthalamide and benzenesulfonylhydrazide, 4,4-oxybenzenesulfonylsemicarbazide and p-toluenesulfonylsemicarbazide, trihydrazinotriazine and mixtures such as citric acid and sodium bicarbonate. Examples of chemical blowing agents are sold under the trade name Safoam TM Various products for sale (Reedy International; Reedy Chemical Foam products).
[0085] Permeability modifiers
[0086] In an embodiment, the composition may further include a permeability modifier. As used herein, the term "permeability modifier" is a compound or composition that reduces the permeability of a blowing agent in a given polyolefin, such that the blowing agent seeps out of a foam made with the polyolefin at a rate approximately the same as the rate at which air diffuses in. This can produce dimensionally stable foam. In the absence of a permeability modifier, the blowing agent (such as isobutane) seeps out of the foam faster than air infiltrates, which may result in dimensional instability of the foam (particularly at low foam densities), resulting in foam shrinkage and deterioration of foam properties.
[0087] Non-limiting examples of permeability modifiers that can be used in various embodiments include C 10 To C 24The amides and esters of fatty acids, as described in U.S. Patent Nos. 3,644,230 and 4,214,054. Esters can also reduce static electricity during and after foam manufacturing. In an embodiment, the permeability modifier includes stearyl stearamide, glyceryl monostearate, glyceryl monobehenate and sorbitol monostearate. The combination of any one of these permeability modifiers is also possible and expected. When used, based on the gross weight of the polymer composition, such permeability modifiers are generally used in an amount ranging from greater than 0 wt % to 10 wt %. For example, based on the gross weight of the polymer composition, the permeability modifier is present in an amount of 0.01 wt %, or 0.1 wt %, or 0.2 wt %, or 0.3 wt %, or 0.5 wt % to 1.0 wt %, or 2.0 wt % or 5.0 wt %. In embodiments, the permeability modifier is present in an amount from 0.01 wt% to 5.0 wt%, or from 0.1 wt% to 2.0 wt%, or from 0.2 wt% to 2.0 wt%, based on the total weight of the polymer composition.
[0088] In an embodiment, the permeability modifier is a fatty acid ester. The fatty acid ester has an alpha-monoester (or monoglyceride) content ranging from 30% to 99%, or 40% to 95%, or 50% to 90%. In an embodiment, the permeability modifier is glyceryl monostearate.
[0089] In embodiments, permeability modifier (for example, glyceryl monostearate) is a component of masterbatch. In such embodiments, permeability modifier (for example, glyceryl monostearate) can be present in the masterbatch in an amount of 0.5 % by weight, or 1 % by weight, or 1.5 % by weight, or 2 % by weight to 2.5 % by weight, or 3.5 % by weight, or 5 % by weight, or 10 % by weight, or 20 % by weight, or 30 % by weight, or 40 % by weight, or 50 % by weight or 60 % by weight. For example, permeability modifier (for example, glyceryl monostearate) can be present in the masterbatch in an amount of 0.5 % by weight to 60 % by weight, or 1 % by weight to 50 % by weight, or 2 % by weight to 30 % by weight, or 5 % by weight to 20 % by weight.
[0090] Extrusion process-foam
[0091] In various embodiments, the composition is used to produce extruded foam. Extruded foam can be produced according to any extruded foam method known and used in the art. For example, it can be heated and blended LDPE-to-PDMS and permeability modifier (such as included) in one or more extruders (e.g., mixing extruder) at a temperature of 140°C to 250°C, or 150°C to 230°C, or 160°C to 220°C, or 170°C to 200°C, or 160°C to 190°C and a pressure of 0.1 MPa to 70 MPa, or 0.5 MPa to 60 MPa, or 1 MPa to 50 MPa, or 2 MPa to 40 MPa, or 3 MPa to 30 MPa, or 4 MPa to 20 MPa, or 6 MPa to 10 MPa (MPa) to form a polymer composition in a flowable state. The polymer composition may also be referred to as an extrudate.
[0092] In embodiments, one or more additional components such as pore nucleating agents, olefin polymers, antistatic agents, pigments, fillers, or other additives known and used in the art may be added to the extrudate along with the LDPE-co-PDMS and permeability modifier.
[0093] When added to the extrudate, the cell nucleating agent promotes the formation of one or more foam cells and can result in smaller cell sizes and higher cell density. In an embodiment, the cell nucleating agent can be talc, calcium carbonate, or a chemical foaming agent. For example, the cell nucleating agent can be added to the extrudate as a talc coating on LDPE-co-PDMS pellets. When included, the cell nucleating agent can be present in an amount of 0.01 wt % to 10.0 wt %, based on the gross weight of the foamable composition.
[0094] Olefin polymers (such as polyethylene or polypropylene) can be included together with LDPE-to-PDMS. For example, in an embodiment, LDPE-to-PDMS can be a kind of polymer in a polymer blend. In an embodiment, LDPE-to-PDMS and one or more polyethylene polymers (such as LDPE) can be blended together and added to an extruder. When present, based on the gross weight of the foamable composition, the olefin polymer can exist in an amount greater than 0 wt % to 99 wt %, 10 wt % to 98 wt %, 20 wt % to 96 wt %, 30 wt % to 95 wt %, 35 wt % to 94 wt % or 40 wt % to 93 wt %.
[0095] Thus, based on the total weight of the foamable composition, the LDPE-co-PDMS may be 1 wt % to 99 wt %, 1 wt % to 95 wt %, 1 wt % to 90 wt %, 1 wt % to 80 wt %, 1 wt % to 70 wt %, 1 wt % to 60 wt %, 1 wt % to 50 wt %, 1 wt % to 25 wt %, 1 wt % to 10 wt %, 10 wt % to 99 wt %, 10 wt % to 95 wt %, 10 wt % to 90 wt %, 10 wt % to 80 wt %, 10 wt % to 70 wt %, 10 wt % to 60 wt %, 10 wt % to 50 wt %, 10 wt % to 25 wt %, 20 wt % to 99 wt %, 20 wt % to 95 wt %, 20 wt % to 90 wt %, 20 wt % to 80 wt %, 20 wt % to 70 wt %, 20 An amount of wt % to 60 wt %, 20 wt % to 50 wt %, 20 wt % to 25 wt %, 30 wt % to 99 wt %, 30 wt % to 95 wt %, 30 wt % to 90 wt %, 30 wt % to 80 wt %, 30 wt % to 70 wt %, 30 wt % to 60 wt %, 30 wt % to 50 wt %, 40 wt % to 99 wt %, 40 wt % to 95 wt %, 40 wt % to 90 wt %, 40 wt % to 80 wt %, 10 wt % to 70 wt %, 40 wt % to 60 wt %, 40 wt % to 50 wt %, 50 wt % to 99 wt %, 50 wt % to 95 wt %, 50 wt % to 90 wt %, 50 wt % to 80 wt %, 50 wt % to 70 wt %, or 50 wt % to 60 wt % is included in the foamable composition.
[0096] In an embodiment, one or more antistatic agents, pigments, fillers or other additives may be included in the composition. Other additives may include, for example, but not limited to, antioxidants, acid scavengers, UV absorbers, flame retardants, processing aids, extrusion aids, etc. When present, such additives may be present in an amount of greater than 0 wt % to 20 wt %, based on the total weight of the foamable composition.
[0097] In embodiments, a physical blowing agent is added to the extruder at a location downstream of the extruder inlet and at a temperature and pressure sufficient to prevent the blowing agent from causing expansion of the polymer composition within the extruder or other suitable melt processing equipment and to enable the blowing agent to be uniformly dispersed within the composition.
[0098] After adding the physical blowing agent, the composition comprising LDPE-co-PDMS, the physical blowing agent and the optional permeability modifier (referred to herein as the "foamable composition") is cooled to the foaming temperature. For example, the foamable composition can be cooled in a cooling extruder. In an embodiment, the foaming temperature is in the range of 10°C lower than the peak melting temperature of LDPE-co-PDMS to 10°C higher than the peak melting temperature of LDPE-co-PDMS. In an embodiment, the foaming temperature is from about 50°C to about 180°C. For example, the foaming temperature can be 70°C to 160°C, 90°C to 140°C, 100°C to 130°C, 100°C to 120°C, 100°C to 110°C, 105°C to 110°C, or 105°C to 118°C.
[0099] Without being bound by theory, it is believed that in embodiments, LDPE-co-PDMS can enable one or more extruder power reductions because, in addition to improved foaming efficiency, the foamable composition also exhibits improved processability through improved lubricity. In addition, it is believed that due to the potentially greater polydispersity index and greater shear thinning of LDPE-co-PDMS, the foamable composition will exhibit less shear heating, which can result in improved cooling on large-scale production lines.
[0100] After cooling to the foaming temperature, in some embodiments, the foamable composition is pushed out of the exit die at the end of the cooling extruder and solidified to form a foam composition. Foaming is completed when the foamable composition exits through the die of the extruder to an area with a lower pressure than the pressure inside the extruder, so that the foamable composition experiences a pressure drop when leaving the exit die of the extruder. The pressure drop causes the physical blowing agent to expand the foamable composition, thereby causing foaming.
[0101] In embodiments, the resulting foam has a OD of less than or equal to 0.200 g / cm2 as measured at 25°C according to ASTM D1622-88. 3 For example, in an embodiment, the foam has a density of 0.015 g / cm 3 Up to 0.200g / cm 3 , 0.025g / cm 3 Up to 0.200g / cm 3 , 0.050g / cm 3 Up to 0.200g / cm 3 , 0.075g / cm 3 Up to 0.200g / cm 3 , 0.090g / cm 3 Up to 0.200g / cm 3 , 0.015g / cm 3 Up to 0.150g / cm 3, 0.025g / cm 3 Up to 0.150g / cm 3 , 0.050g / cm 3 Up to 0.150g / cm 3 , 0.075g / cm 3 Up to 0.150g / cm 3 , 0.090g / cm 3 Up to 0.150g / cm 3 , 0.015g / cm 3 Up to 0.100g / cm 3 , 0.025g / cm 3 Up to 0.100g / cm 3 , 0.050g / cm 3 Up to 0.100g / cm 3 , 0.075g / cm 3 Up to 0.100g / cm 3 or 0.090g / cm 3 Up to 0.100g / cm 3 In embodiments, the foam is an open-cell foam, while in other embodiments, the foam is a closed-cell foam. For example, in embodiments, the foam may have a density of 0.090 g / cm 3 Up to 0.200g / cm 3 As another example, in an embodiment, the foam may be an open-cell foam having a density of 0.015 g / cm 3 Up to 0.200g / cm 3 Density of closed cell foam.
[0102] use
[0103] Embodiments of the silicone-functionalized polyethylene foams described herein can be in any known physical form, including but not limited to extruded sheets, rods, plates, films, and the like. Such foams can be used, for example, in cushioned packaging, sports and leisure products, egg cartons, meat trays, building and construction, sound insulation, pipe insulation, gaskets, vibration pads, luggage liners, table mats, shoe holes, gym mats, greenhouse insulation pads, container swabs, absorbent foams (e.g., for cleaning oil spills, for health and hygiene applications, etc.), and display foams. Other applications such as insulation for refrigeration, buoyancy applications, and floral and craft applications are contemplated and possible.
[0104] Test Method
[0105] The test methods include the following:
[0106] Melt index (I2)
[0107] Melt index (I2) is measured according to ASTM D-1238 at 190°C under 2.16 kg. Values are reported in g / 10 min (or dg / min), which corresponds to grams eluted per 10 minutes.
[0108] density
[0109] The density of the foam is measured according to ASTM D1622-88 at 25°C and is expressed in grams per cubic centimeter (g / cc or g / cm 3 The density of a polymer is measured according to ASTM D792 at 25°C and is reported in grams per cubic centimeter (g / cc or g / cm 3 ) as the unit to report.
[0110] Melt Strength
[0111] Melt strength measurements were performed on a Gottfert Rheotens 71.97 (Gottfert Inc.; Rock Hill, SC) attached to a Gottfert Rheotester 2000 capillary rheometer. Melt samples (about 25 to 30 grams) were run through a 180 degree flat entry rheometer equipped with a 30 mm long, 2.0 mm diameter, and an aspect ratio (length / diameter) of 15. Rheotester 2000 capillary rheometer feed. After equilibrating the sample at 190°C for 10 minutes, the piston was operated at a constant piston speed of 0.265 mm / s. The standard test temperature is 190°C. The sample was uniaxially stretched to a set of accelerating nipples located 100 mm below the die, with an acceleration of 2.4 mm / s 2 The tensile force is recorded as a function of the take-up speed of the roll. The melt strength is reported as the flatline force (cN) before the strand breaks. The following conditions are used in the melt strength measurements: plunger speed = 0.265 mm / s; wheel acceleration = 2.4 mm / s 2 ; Capillary diameter = 2.0 mm; Capillary length = 30 mm; and Barrel diameter = 12 mm.
[0112] DSC crystallinity
[0113] Differential scanning calorimetry (DSC) can be used to measure the crystallinity of a sample over a wide temperature range at a given temperature. For example, a TA model Q1000DSC (TA Instruments, New Castle, DE) equipped with an RCS (refrigerated cooling system) cooling attachment and an autosampler module was used for testing. During the test, a nitrogen purge gas flow of 50 ml / min was used. The resin was compression molded into a 3 mm thick × 1 inch circular sheet at 350 ° C for 5 minutes in air at 1500 psi pressure. The sample was then removed from the press and placed on a counter to cool to room temperature (approximately 25 ° C). A 3-10 mg sample of the cooling material was cut into a 6 mm diameter disc, weighed, placed in a lightweight aluminum pan, and rolled up. The thermal properties of the sample were then tested.
[0114] The thermal properties of the sample are determined by varying the sample temperature up and down to produce a response versus temperature curve. First, the sample is rapidly heated to 180°C and held isothermally for 3 minutes to remove any previous thermal history. Next, the sample is cooled to -40°C at a cooling rate of 10°C / min and held at -40°C for 3 minutes. The sample is then heated to 150°C at a heating rate of 10°C / min. The cooling curve and the second heating curve are recorded. The value determined is the peak melting temperature (T m ), peak crystallization temperature (T c ), heat of fusion (H f ) (in J / g), and the percent crystallinity of the polyethylene sample calculated using the following Equation 1:
[0115]
[0116] Report the heat of fusion (H) from the second heating curve. f ) and the peak melting temperature. The peak crystallization temperature is determined from the cooling curve.
[0117] Gel Permeation Chromatography (GPC)
[0118] The GPC system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5) coupled to a Precision Detectors (now Agilent Technologies, Amherst, MA) 2-angle light scattering (LS) detector model 2040 and 4 capillary solution viscometers (DV). A GPC with the last two independent detectors and at least one of the first detectors is sometimes referred to as a "3D-GPC", while the term "GPC" alone usually refers to "conventional GPC". For all absolute light scattering measurements, a 15 degree angle was used for the measurements. The autosampler oven chamber was operated at 160°C, and the column chamber was operated at 150°C. The columns used were 4 Agilent "MixedA" 30 cm 20 micron linear mixed bed columns. The chromatographic solvent used was 1,2,4 trichlorobenzene and contained 200 ppm of butylated hydroxytoluene (BHT). The solvent source was purged with nitrogen. The polyethylene sample was gently stirred at 160°C for four hours. The injection volume was 200 μL. The flow rate through the GPC was set to 1 mL / min.
[0119] The GPC column set was calibrated prior to running the sample by running at least twenty narrow molecular weight distribution polystyrene standards. The molecular weight (Mw) range of the standards was from 580 grams per mole to 8,400,000 grams per mole, and the standards were contained in 6 "cocktail" mixtures. Each standard mixture was separated by at least one decade between individual molecular weights. The standard mixtures were purchased from Agilent Technologies. The polystyrene standards were prepared as follows: 0.025 g in 50 mL of solvent for molecular weights equal to or greater than 1,000,000 g / mol; and 0.05 g in 50 mL of solvent for molecular weights less than 1,000,000 g / mol. The polystyrene standards were dissolved by gentle stirring at 80°C for 30 minutes. The narrow standards mixtures were run first, and in descending order of the highest molecular weight component to minimize degradation. Polystyrene standard peak molecular weights were converted to polyethylene molecular weights using Equation 2 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):
[0120] M 聚乙烯 =A×(M 聚苯乙烯 ) B (Equation 2)
[0121] Where M is the molecular weight of polyethylene or polystyrene (as labeled), A has a value of 0.43, and B equals 1.0.
[0122] A polynomial between the 3rd and 5th order was used to fit the corresponding polyethylene equivalent calibration points. Total plate counts for the GPC column set were performed with eicosane (prepared at 0.04 g in 50 ml TCB and dissolved for 20 minutes under gentle stirring). Plate counts (Equation 3) and symmetry (Equation 4) were measured at 200 μL injection according to the following equations:
[0123]
[0124] Where RV is the retention volume in mL, Peak Width is in mL, Peak Maximum is the maximum height of the peak, and 1 / 2 Height is the height of 1 / 2 the Peak Maximum.
[0125]
[0126] Where RV is the retention volume in mL, and peak width is in mL, peak maximum is the maximum position of the peak, tenth height is 1 / 10 of the height of the peak maximum, and where post-peak refers to the tail of the peak with a retention volume later than the peak maximum, and where pre-peak refers to the front of the peak with a retention volume earlier than the peak maximum. The plate count of the chromatographic system should be greater than 24,000, and the symmetry should be between 0.98 and 1.22.
[0127] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set to 2 mg / ml and the solvent (containing 200 ppm BHT) was added to a septum-capped vial previously sparged with nitrogen by the PolymerChar high temperature autosampler. The samples were dissolved at 160°C for 2 hours under "slow" shaking.
[0128] Based on the GPC results, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer, according to Equations 5-7, the PolymerChar GPCOne TM The software, the baseline-subtracted IR chromatogram at each equidistant data collection point (i), and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 2 were used to determine Mn. (GPC) 、Mw (GPC) and Mz (GPC) Calculation.
[0129]
[0130] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate for each sample (Flow Rate (Nominal)) by comparing the RV of the corresponding decane peak in the sample (RV (FM Sample)) with the RV of the decane peak in the narrow standard calibration (RV (FM Calibrated)). It was then assumed that any changes in the decane marker peak time were related to linear changes in the flow rate (Flow Rate (Effective)) throughout the run. To facilitate the highest accuracy in the RV measurement of the flow marker peak, the peak of the flow marker concentration chromatogram was fit to a quadratic equation using a least squares fitting procedure. The first derivative of the quadratic equation was then used to solve for the true peak position. After the system was calibrated based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated according to Equation 8. Processing of the flow marker peak was performed by the PolymerCharGPCOne TM The acceptable flow rate correction is such that the effective flow rate should be within + / - 2% of the nominal flow rate.
[0131]
[0132] PDI is calculated as Mw divided by Mn (ie, Mw / Mn).
[0133] Triple Detector GPC (3D-GPC)
[0134] The chromatography system, running conditions, column settings, column calibration and calculation of conventional molecular weight moments and distributions were performed according to the methods described in Gel Permeation Chromatography (GPC).
[0135] To determine the offset of the viscometer and light scattering detectors relative to the IR5 detector, a systematic approach for determining the offset of multiple detectors was performed in a manner consistent with that published by Balke, Mourey et al. (Mourey and Balke, Chromatorgraphy Polym., Chapter 12, (1992)) (Balke, Thitiratsakul, Lew, Cheung, Mourey, Chromatorgraphy Polym., Chapter 13, (1992)) using the PolymerChar GPCOne TM The software optimizes the triple detector logarithm (Mw / Mn>3) from a broad homopolymer polyethylene standard. w and intrinsic viscosity) results with the narrow standards column calibration results from the narrow standards calibration curve.
[0136] Absolute molecular weight data were obtained in a manner consistent with that published by Zimm (Zimm, BH, J. Chem. Phys., 16, 1099 (1948)) and Kratochvil (Kratochvil, P., Classical Light Scattering from Polymer Solutions, Elsevier, Oxford, NY (1987)). The total injected concentration used to determine the molecular weight was obtained from the mass detector area and the mass detector constant, which was derived from a suitable linear polyethylene homopolymer or one of the polyethylene standards of known weight average molecular weight. The calculated molecular weight (using GPCOne TM ) are obtained using light scattering constants derived from one or more of the mentioned polyethylene standards and a refractive index concentration coefficient dn / dc of 0.104. In general, the mass detector response (IR5) and light scattering constants (using GPCOne TM Viscometer calibration (using GPCOne TM The viscometer constant (determined using GPCOne TM The specific viscosity area (DV) and injected mass of the calibration standards are related to their intrinsic viscosity. The chromatographic concentrations are assumed to be low enough to eliminate the effect of the 2nd viral coefficient (the effect of concentration on molecular weight).
[0137] Absolute weight average molecular weight (Mw (Abs) ) is (using GPCOne TM ) is obtained from the area of the light scattering (LS) integrated chromatogram (calculated from the light scattering constant) divided by the mass recovered from the mass constant and the mass detector (IR5) area. Molecular weight and intrinsic viscosity responses are at the end of the chromatogram where the signal-to-noise ratio becomes low (using GPCOne TM ) linear extrapolation. Other corresponding moments Mn (Abs) and Mz (Abs) The calculation according to equation 9-10 is as follows:
[0138]
[0139] PDI is calculated as Mw divided by Mn (ie, Mw / Mn).
[0140] High Temperature Liquid Chromatography (HTLC)
[0141] High temperature liquid chromatography (HTLC) was used for the separation and characterization of Si-PE hybrids. Free PDMS was quantified by external standard calibration method. A sample solution of ~2.0 mg / mL was prepared in anhydrous decane. The sample was dissolved using a laboratory heated oscillator at 130°C for ~1 hour. The sample solution was then transferred to the PolymerChar autosampler. Prior to injection, the sample solution was reheated and oscillated at 130°C for 1 hour by a heated oscillator in the PolymerChar. HTLC is based on the PolymerChar high temperature 2DLC / GPC instrument. The LC pump was an Agilent 1260 HPLC system with a flow rate set to 1.0 mL / min. The injection loop was 20 μL of solution. A Thermo-Fisher hypercarb column (4.6 mm inner diameter (id) × 100 mm length (l.), 5 um particle size and The separation was performed using an Agilent HT-ELSD detector (model G7826A) with a nebulizer temperature set at 160°C; an evaporator temperature of 120°C, and a N2 flow rate of 0.2 SLM. A gradient of decane and ODCB was applied in the separation. Data were collected by PolymerChar software version 1.1 and reduced by Agilent SEC software Cirrus 3.3.
[0142] Table 1 :
[0143]
[0144] Nuclear Magnetic Resonance (NMR)
[0145] The samples were prepared by adding 0.1 to 0.2 g of sample to 3.25 g of 50 / 50 (by weight) tetrachloroethane-d2 / perchloroethylene with 0.001 M Cr(AcAc)3 in a Norell 1001-7 10 mm NMR tube. The samples were purged by bubbling N2 through the solvent via a pipette inserted into the tube for approximately 5 minutes to prevent oxidation, capped, and sealed with Teflon tape. The samples were heated and vortexed at 115-135°C to ensure homogeneity. The spectrometers were run on a Bruker AVANCE 600 MHz spectrometer equipped with a Bruker 10 mm CryoProbe and a sample temperature of 120°C. 1H NMR. Collect the spectrum using ZG pulse, 16 scans, AQ 1.8s, D1 14s. Set the polymer integral from about 0.6ppm to 2.6ppm to an arbitrary value. Divide this value by 2 to get the total moles of CH2s of the polymer. Multiply the total moles of CH2 by 14g / mol to get the polymer weight. The PDMS integral from about -0.3ppm to 0.6ppm is divided by 6 to get the moles of PDMS units. Multiply by 74.1g / mol PDMS units to get the PDMS weight. Use the two weights to calculate the wt% PDMS.
[0146] Example
[0147] The following examples illustrate features of the present disclosure but are not intended to limit the scope of the present disclosure.
[0148] Example 1
[0149] f-PDMS is formed as a 1:2:1 mixture of the following three siloxanes:
[0150]
[0151] The polymerization was carried out in a 300 mL continuous stirred tank reactor (CSTR) heated to 220° C. using four electric heating bands. The agitator speed was 1800 revolutions per minute (RPM). The reactor pressure was controlled to be approximately 193 MPa. Propylene was used as a chain transfer agent. Ethylene and propylene were fed to the top of the reactor along the stirring shaft at a flow rate of 5440-5470 g / h of ethylene at the ratio reported in Table 1 below. TPA and TPO were used as initiators in a mass ratio of 0.61:1. The initiator was diluted in ISOPAR E (available from ExxonMobil Chemical Co.) and injected into the reactor side at a pressure of 193 MPa at a ratio of 30-33 mass ppm TPA and 50-54 mass ppm TPO to ethylene. f-PDMS was diluted to 30% by weight in ethyl acetate (available from Sigma Aldrich) and injected into the reactor side separately at a flow rate reported in Table 1 below.
[0152] The reactor residence time is about 1.5 minutes. All unreacted reactants and polymers are discharged through a single outlet located at the bottom of the reactor. The LDPE-to-PDMS polymer is then separated from the remaining reactants by atomization, the stream is depressurized to about 0.1 MPa and the stream is cooled to ambient temperature simultaneously. The LDPE-to-PDMS polymer in powder form is then collected.
[0153] The process conditions for preparing LDPE-co-PDMS polymers are reported in Table 2.
[0154] Table 2 :
[0155]
[0156] High temperature liquid chromatography (HTLC) was used for the separation and characterization of Si-PE hybrids. Free PDMS was quantified by external standard calibration method.
[0157] DSC analysis of LDPE-co-PDMS was performed and showed a peak melting temperature of 107.7°C and a heat of fusion of 136.1 J / g.
[0158] The samples were also analyzed using conventional GPC and 3D-GPC. Table 3 reports the molecular weight characteristics of the samples.
[0159] Table 3 :
[0160]
[0161] For comparison, DSC, conventional GPC, and 3D-GPC were used to measure the DOW TM LDPE 450E was analyzed. It exhibited a peak melting temperature of 110.8°C and a heat of fusion of 157.5 J / g. Table 4 reports the DOW TM Molecular weight properties of LDPE 450E.
[0162] Table 4 :
[0163]
[0164] Thus, from the above data it can be seen that LDPE-co-PDMS has a lower peak melting temperature and heat of fusion, as well as (in this particular case) an increased PDI.
[0165] LDPE-co-PDMS and DOW TM Melt Strength of Both LDPE 450E. LDPE-co-PDMS exhibits a melt strength of about 8 to 9 cN at 190°C, which is similar to that of LDPE 450E.
[0166] pass 1H NMR estimated the amount of both attached and unattached PDMS and showed 7.77 wt% PDMS in LDPE-co-PDMS. The amount of unattached f-PDMS was estimated by using HTLC analysis. The average of two replicates was 3.0 wt% unattached PDMS in LDPE-co-PDMS.
[0167] LDPE-co-PDMS exhibits a melt index of about 3.5 dg / min. TM LDPE 450E has a melt index of 2.0 dg / min. TM The density of LDPE 450E is 0.923 g / cc, and the density of LDPE-co-PDMS is 0.9256 g / cc.
[0168] Example 2
[0169] Next, use LDPE-co-PDMS and / or DOW TM The foam was prepared using LDPE 450E. The foam composition was prepared using a tandem extrusion system having a mixing extruder and a cooling extruder fed through the mixing extruder. The mixing extruder was a co-rotating twin screw extruder with a 34 mm diameter screw that was specifically configured to ensure good mixing of the polymer composition and the blowing agent while forming the foamable composition. The mixing extruder was operated at a screw speed of 55 rpm and a set temperature of 180°C across all zones.
[0170] The cooling extruder was a single screw extruder with a 40 mm diameter screw. The barrel temperature and die temperature of the cooling extruder were controlled in four zones using separate oil heaters. Zone 1 and zone 2 were operated at set temperatures of 129° C. and 116° C., respectively. The set temperature of zone 3 was the foaming temperature of the foamable composition. The cooling extruder was operated at a screw speed of 22 rpm. A 3 mm diameter rod die was attached to the end of the cooling extruder. The temperature of the die was maintained at 125° C.
[0171] The components of polymer composition are dry mixed, and then fed into the entrance of mixing extruder by solid metering feeder.Realize the complete melting of polymer component, and use positive displacement pump (double piston HPLC pump) that whipping agent (isobutane) is injected into the mixing extruder with the 20L / D of extruder.The flow velocity of polymer is maintained at 36 grams per minute (g / min).The residence time from solid component being added in the extruder entrance until the method for outlet die is 12 minutes.
[0172] Foams of different compositions and densities were produced under various processing conditions, as shown in Table 5. In particular, Examples 1 to 4 contained LDPE-co-PDMS, while CS1 was prepared using only LDPE.
[0173] HS-E01 is a masterbatch of glycerol monostearate (GMS), a permeability modifier, in a LDPE carrier resin. It is available from Polyvel and has the following properties: 50% GMS content, 90% alpha monomer content, white color, melt index of 320 g / 10 min, and softening point of 70°C.
[0174] Mistron Vapor R is a talc having a median particle size of 2.2 μm and is available from Imerys Talc.
[0175] Table 5 :
[0176]
[0177] * Example 3 is a visual observation during the transition from Example 2 to Example 4.
[0178] For CS1 and each of Examples 1-4, GMS was present in the polymer composition in an amount of 1 wt %, and isobutane was present in the foamable composition in an amount of 9 wt %.
[0179] As reported in Table 5, Examples 1, 2, and 3 are closed cell structures, while the foam of Example 4 is predominantly open cell. In general, such open cell structures cannot be obtained with LDPE, even over a wide range of foaming temperatures. Additionally, the compositions of Examples 1 to 4 tend to exhibit lower extruder amperages than that of CS1, which may be due in part to the presence of silicone in the LDPE-co-PDMS.
[0180] Furthermore, using a fixed amount of isobutane blowing agent, the closed cell foams of Examples 1 to 3 have a density significantly lower than the foam of CS1. Example 3 relates to a visual observation made during the transition from Example 2 to Example 4, where a significant increase in the diameter of the foamed extrudate was observed, indicating that the foam density was lower about halfway through the transition. The improved foaming efficiency observed in the examples including LDPE-co-PDMS is a valuable attribute that can reduce metering and reduce the amount of blowing agent required for a given foam density. Without being bound by theory, improved foaming efficiency can also mean reduced blowing agent permeability and / or increased blowing agent solubility, which can be beneficial when using fast penetrating blowing agents (such as carbon dioxide).
[0181] In addition, due to the silicone present in LDPE-co-PDMS and the relatively large polydispersity index (PDI; reported in Tables 1 and 2) and greater shear thinning of the LDPE-co-PDMS used in Examples 1 to 4, less shear heating and better cooling are expected on large-scale (e.g., commercial) extrusion foaming lines.
[0182] Obviously, modifications and variations are possible without departing from the scope of the present disclosure as defined in the appended claims.More specifically, although some aspects of the present disclosure are identified herein as preferred or particularly advantageous, it is contemplated that the present disclosure is not necessarily limited to these aspects.
Claims
1. An extruded foam formed from a composition comprising: 1 to 99 weight percent of a silicone-functionalized polyethylene comprising the polymerization reaction product of ethylene and a (meth)acrylate-functionalized polydimethylsiloxane; and Physical foaming agents; wherein the foam has a relative humidity of less than or equal to 0.200 g / cm2 as measured at 25°C according to ASTM D1622-88. 3 density. 2 . The extruded foam of claim 1 , wherein the silicone functionalized polyethylene has a polydispersity index (PDI) of 3 to 14. 3 .
3. The extruded foam of claim 1, wherein the silicone-functionalized polyethylene comprises one or more of the following structures: Where R 1 R is a bridge group connecting the functional group (meth)acrylate and siloxane. 2 is a terminal group selected from an alkyl group, a substituted alkyl group, an aryl group, an alkenyl group, H and OH, x is an integer from 10 to 1000, and y is an integer from 1 to 20.
4. The extruded foam of claim 1 wherein the composition further comprises from greater than 0 wt% to 99 wt% of an olefin polymer.
5. The extruded foam of claim 4, wherein the olefin polymer comprises LDPE.
6. The extruded foam of claim 1, wherein the composition further comprises greater than 0 wt% to 2 wt% of a permeability modifier.
7. The extruded foam of claim 6, wherein the permeability modifier comprises C 10 To C 24 Amides or esters of fatty acids.
8. The extruded foam of claim 1, wherein the physical blowing agent comprises carbon dioxide, a hydrocarbon, or a mixture thereof.
9. The extruded foam of claim 1, wherein the physical blowing agent is present in an amount of 5 wt% to 20 wt%.
10. The extruded foam of claim 1 wherein the foam is open-cell.
11. The extruded foam of claim 10, wherein the foam has a relative humidity of 0.090 g / cm 3 Up to 0.200g / cm 3 density.
12. The extruded foam of claim 1 wherein the foam is closed cell.
13. The extruded foam of claim 12, wherein the foam has a relative humidity of 0.015 g / cm 3 Up to 0.200g / cm 3 density.
14. The extruded foam of claim 8, wherein the hydrocarbon is selected from isobutane, n-butane, isomers of pentane, or mixtures thereof.
Citation Information
Patent Citations
Extrusion process for polyolefin foam
US3644230A
Expanded olefin polymer
US4214054A
Interpolymers of ethylene and unsaturated carboxylic acids
US4599392A
Polysiloxane compound which is stable during storage and produces vulcanisates which can be permanently wetted with water
US6239244B1
Polydimethylsiloxane grafted polyethylene foam
CN106575545A